Penerapan Prinsip Character Dalam Pelaksanaan Prinsip Kehati-hatian pada Analisis Pemberian Kredit Usaha Mikro - Rahmadi Indra Tektona; Qoriatur Risma (Faculty of Law, Universitas Pattimura, 2020)
Credit is the ability to carry out a purchase or make a loan with a promise that payment will be deferred at an agreed time period. One financial institution that can provide credit is the bank, when providing credit the bank not only uses its own capital but also uses the customer's funds that have been entrusted to the bank. When providing credit, the bank cannot avoid the risk of non-performing loans, related to this, the bank applies the precautionary principle that is realized by the existence of the 5C principle, one of which is character. The application of the character principle aims to assess the character or character of the prospective debtor, whether the prospective debtor has a good character or is not good. The purpose of this paper is to analyze the factors driving and inhibiting the implementation of character principles in the analysis of micro business credit as a form of implementing prudential principles at Bank Mandiri Jember Branch. The type of research used by the author is Empirical Juridical. Then the method used is a qualitative approach method. The results of this research are the driving factors consisting of several factors, among others, in order to make credit activities run safely, minimize losses, ensure the smooth delivery of credit facilities, and build cooperation and trust between banks and customers for a long period of time. Related to the inhibiting factors consist of non-cooperative customers, bad faith in bank management, human resources, and proximity.